MBS (methyl methacrylate-butadiene-styrene) resin and preparation method thereof
By coating the hard monomer layer on the rubber core of the MBS resin and agglomerate with acid polymer emulsion, the problems of difficulty in particle size control and low product purity in the preparation of existing MBS resins are solved, and excellent impact resistance and yellowing resistance are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411949367.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing MBS resin preparation methods have problems such as difficulty in controlling particle size, poor repeatability, low product purity and impurity residue, which affects its impact resistance and transparency.
By coating the hard monomer layer on the rubber core and agglomerate with an acid polymer emulsion, an MBS resin with a shell structure is formed to improve its impact resistance and yellowing resistance.
It realizes the excellent impact resistance and yellowing resistance of MBS resin, while simplifying the preparation process, mild conditions, easy to control, and is suitable for industrial production.
Smart Images

Figure CN119638909A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resin preparation, and in particular relates to an MBS resin and a preparation method thereof. Background Art
[0002] MBS resin is mainly composed of butadiene (BD), styrene (ST) and methyl methacrylate (MMA) and is prepared by emulsion polymerization. MBS has a typical core / shell structure in submicroscopic morphology, with styrene-butadiene rubber constituting the rubber phase and methyl methacrylate-styrene copolymer constituting the resin phase. Due to the special structure of MBS resin, MBS resin has good transparency, impact resistance, surface finish and easy processing performance. Compared with other impact modifiers, MBS resin can maintain the transparency of the product to the maximum extent while toughening it. It is widely used in the processing and application of plastics such as PVC, PC, PC / ABS alloy, PBT, PMMA, etc., and the addition amount is generally 2-5%.
[0003] The rubber particle size is in the range of 200-300nm and has excellent impact resistance. A large particle size can be obtained through a one-step synthesis process, but it has the disadvantages of being time-consuming, inefficient, and complex to operate. Large particle size can also be obtained by agglomerating small particles. The existing agglomeration method is to use a high-valent salt solution to reduce the stability of the emulsion, thereby increasing the particle size. The agglomeration process of this method is difficult to control, has poor repeatability, and the particle sizes of emulsions produced in different batches vary greatly; the emulsion has poor stability after agglomeration and is easy to agglomerate. Moreover, a large amount of impurities will inevitably remain in the system after treatment by this method, which are difficult to remove during the reaction, affecting the purity of the final product and affecting the performance of the final product. Summary of the invention
[0004] The invention provides an MBS resin and a preparation method thereof. The MBS resin provided by the invention has excellent impact resistance and is not prone to yellowing. The preparation method is simple, the conditions are mild, the process is easy to control, and industrialized production can be realized.
[0005] In order to achieve the above object, the present invention provides an MBS resin, comprising a rubber core and a shell layer, wherein the shell layer comprises a hard monomer layer and a thermoplastic resin layer;
[0006] The hard monomer layer is wrapped on the rubber core to obtain a latex coated with the hard monomer layer, the acid polymer emulsion agglomerates a plurality of latexes coated with the hard monomer layer to form an agglomerated latex, and the thermoplastic resin layer is wrapped on the agglomerated latex;
[0007] The total weight of the rubber core, the hard monomer layer and the thermoplastic resin layer is 100 parts, including 60 to 80 parts of the rubber core, 1 to 10 parts of the hard monomer layer and 10 to 40 parts of the thermoplastic resin layer;
[0008] The raw materials of the hard monomer layer include vinyl monomers and / or alkyl methacrylate; the thermoplastic resin layer is obtained by grafting alkyl methacrylate and aromatic vinyl monomer; the raw materials of the acidic polymer emulsion include alkyl acrylate and unsaturated acid.
[0009] Preferably, the rubber core is obtained by polymerizing a conjugated diene monomer, or by polymerizing a conjugated diene monomer and a vinyl monomer that can polymerize with the conjugated diene monomer.
[0010] Preferably, the raw materials for preparing the rubber core include, by weight:
[0011] 50-100 parts of conjugated diene monomer, 0-50 parts of vinyl monomer capable of polymerizing with conjugated diene monomer, 0-1.5 parts of chain transfer agent and 0-5 parts of crosslinking monomer, 0.5-4 parts of emulsifier, 0.5-1.2 parts of oxidant, 0-1.2 parts of electrolyte, 0.001-0.5 of reducing agent and 0.002-0.15 parts of complexing agent.
[0012] Preferably, the raw materials for preparing the hard monomer include, by weight:
[0013] 0 to 6 parts of vinyl monomer, 0 to 0.2 parts of crosslinking monomer, 0.05 to 0.3 parts of oxidant, 0 to 6 parts of alkyl methacrylate, 0.01 to 0.5 parts of reducing agent and 0 to 0.3 parts of emulsifier.
[0014] Preferably, the raw materials for preparing the acidic polymer emulsion include, by weight:
[0015] 85-97 parts of alkyl acrylate, 3-15 parts of unsaturated acid, 0.5-3 parts of emulsifier, 0-1 part of electrolyte, 0-0.5 part of chain transfer agent and 0.1-1 part of oxidant.
[0016] Preferably, by weight, the raw materials for grafting include:
[0017] 4-18 parts of alkyl methacrylate, 6-22 parts of aromatic vinyl monomer, 0.1-1 parts of emulsifier, 0.05-0.7 parts of oxidant, 0-0.25 parts of electrolyte, 0.01-0.5 parts of reducing agent, 0-0.25 parts of chain transfer agent and 0-1 parts of crosslinking monomer.
[0018] Preferably, the mass ratio of the acidic polymer emulsion to the latex coated with the hard monomer layer is 0.1 to 3:100.
[0019] Preferably, the particle size of the rubber core is 40 to 60 nm; the particle size of the latex after agglomeration is 120 to 260 nm; and the particle size of the MBS resin is 180 to 280 nm.
[0020] The present invention provides a method for preparing the MBS resin described in any one of the above, comprising the following steps:
[0021] 1) using rubber latex as a rubber core and coating the rubber latex with a hard monomer to obtain a latex coated with a hard monomer layer;
[0022] 2) adding an acidic polymer latex to the latex coated with the hard monomer layer for agglomeration to obtain an agglomerated latex;
[0023] 3) Grafting is performed on the agglomerated latex to obtain MBS resin.
[0024] Preferably, the method for preparing the rubber latex in step 1) comprises the following steps:
[0025] a. Pre-emulsifying the mixture by mixing an emulsifier, an oxidant, an electrolyte, a chain transfer agent, a crosslinking monomer, a vinyl monomer capable of polymerizing with a conjugated diene monomer, and water to obtain a pre-reaction solution;
[0026] b. Under the protection of an inert atmosphere, a conjugated diene monomer is added to the pre-reaction liquid, and after the temperature is raised to the reaction temperature, a reducing agent and a complexing agent are added to react to obtain a rubber latex.
[0027] Preferably, the acidic polymer emulsion in step 2) is prepared by the following steps:
[0028] (1) mixing an alkyl acrylate, an unsaturated acid, an emulsifier, an electrolyte, a chain transfer agent, an oxidant and water, and emulsifying the mixture to obtain a pre-emulsion;
[0029] (2) heating 25% to 35% of the total amount of the pre-emulsion obtained in step (1) to 70 to 75° C., heating the system to 80 to 85° C. after the system turns blue, and dripping the remaining pre-emulsion into the heated pre-emulsion to obtain an acidic polymer emulsion.
[0030] Preferably, in step 3), grafting is performed on the agglomerated latex by continuous or intermittent feeding;
[0031] The continuous feeding method is: mixing the grafted raw materials, adding the obtained mixed material into the agglomerated latex to carry out grafting reaction, and obtaining the MBS resin;
[0032] The intermittent feeding method comprises the following steps:
[0033] ① Adding part of the oxidant and the chain transfer agent to the agglomerated latex, and continuously dropping a mixed emulsion of aromatic vinyl monomer, water, part of the emulsifier, part of the reducing agent and electrolyte to carry out a grafting reaction to obtain a pre-product of MBS resin;
[0034] ② Add the remaining oxidant to the pre-product of MBS resin, and then continuously drop a mixed emulsion of alkyl methacrylate, water, the remaining emulsifier, the remaining reducing agent and the cross-linking agent to carry out a grafting reaction to obtain MBS resin.
[0035] Compared with the prior art, the advantages and positive effects of the present invention are:
[0036] The MBS resin provided by the present invention is coated with a layer of hard monomer on the rubber core, and the rubber core is agglomerated by adding an acidic polymer emulsion to the rubber core coated with the hard monomer layer. There are a large number of carboxylic acid groups in the molecules of the acidic polymer emulsion, and the carboxylic acid groups can penetrate the inner coating layer. The carboxyl groups form chemical bonds with the unsaturated bonds in the rubber latex to gather the rubber cores together. Since the outer layer of the rubber core seed is coated with a hard layer, particles with a clustered structure that is not fused are formed. The internal structure of the particles formed by this process is relatively tight, and there are partial gaps. There are also protrusions on the surface of the particles, so that a large impact strength can be maintained. And this structure is coated with a layer of hard monomer on the surface of polybutadiene, which can form a closed layer, better prevent polybutadiene from being oxidized, and thus improve the yellowing resistance. At a relatively high processing temperature (250-260°C), it can still maintain excellent high temperature yellowing resistance.
[0037] Furthermore, the preparation method of MBS provided by the present invention is simple, the conditions are mild, the process is easy to control, and industrialized production can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the structure of the MBS resin prepared by the present invention. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The present invention provides an MBS resin, comprising a rubber core and a shell layer, wherein the shell layer comprises a hard monomer layer and a thermoplastic resin layer; the hard monomer layer is wrapped on the rubber core to obtain a latex coated with the hard monomer layer, an acidic polymer emulsion agglomerates a plurality of latexes coated with the hard monomer layer to form an agglomerated latex, and the thermoplastic resin layer is wrapped on the agglomerated latex; wherein the total weight of the rubber core, the hard monomer layer and the thermoplastic resin layer is 100 parts, comprising 60 to 80 parts of the rubber core, 1 to 10 parts of the hard monomer layer and 10 to 40 parts of the thermoplastic resin layer; the raw material of the hard monomer layer comprises vinyl monomer and / or alkyl methacrylate; the thermoplastic resin layer is obtained by grafting alkyl methacrylate and aromatic vinyl monomer; the raw material of the acidic polymer emulsion comprises alkyl acrylate and unsaturated acid. In the present invention, if the amount of rubber is too small, the effect of improving the impact strength of the matrix cannot be achieved; if the amount of rubber is too large, the powder performance thereof deteriorates and it is difficult to obtain a powder product. It can be understood that the dosage ratio defined in the present invention is the optimal ratio.
[0041] The present invention coats the rubber core with a layer of hard monomer, and by adding an acidic polymer emulsion to the rubber core coated with the hard monomer layer, the rubber core can be agglomerated. There are a large number of carboxylic acid groups in the molecules of the acidic polymer emulsion. The carboxylic acid groups can penetrate the inner coating layer, and the carboxyl groups form chemical bonds with the unsaturated bonds in the rubber latex to gather the rubber cores together. Since the outer layer of the rubber core seed is coated with a hard layer, particles with a clustered structure that is aggregated but not fused are formed. The particles formed by this process have a tighter internal structure, and there are partial gaps. There are also protrusions on the surface of the particles, so that they can maintain a greater impact strength. In addition, this structure coats a layer of hard monomer on the surface of polybutadiene to form a closed layer, which better prevents polybutadiene from being oxidized, thereby improving the yellowing resistance. The MBS resin in the present invention is such as Figure 1 As shown, a hard monomer layer is coated on the outside of the rubber core, and a number of latexes coated with the hard monomer layer are agglomerated together to form particles with a clustered structure that is not fused, and styrene and methyl methacrylate are coated on the aggregated latex.
[0042] The present invention provides a method for preparing the MBS resin described in any one of the above, comprising the following steps:
[0043] 1) using rubber latex as a rubber core and coating the rubber latex with a hard monomer to obtain a latex coated with a hard monomer layer;
[0044] 2) adding an acidic polymer latex to the latex coated with the hard monomer layer for agglomeration to obtain an agglomerated latex;
[0045] 3) Grafting is performed on the agglomerated latex to obtain MBS resin.
[0046] The present invention uses rubber latex as a rubber core, and coats the rubber latex with a hard monomer to obtain a latex coated with a hard monomer layer. In the present invention, the raw materials for preparing the rubber latex in step 1) preferably include, by weight, 50 to 100 parts of a conjugated diene monomer, 0 to 50 parts of a vinyl monomer that can be polymerized with the conjugated diene monomer, 0 to 1.5 parts of a chain transfer agent and 0 to 5 parts of a crosslinking monomer, 0.5 to 4 parts of an emulsifier, 0.5 to 1.2 parts of an oxidant, 0 to 1.2 parts of an electrolyte, 0.001 to 0.5 parts of a reducing agent, and 0.002 to 0.15 parts of a complexing agent.
[0047] In the present invention, the conjugated diene monomer is preferably one or more of butadiene, isoprene and chloroprene. In the present invention, the vinyl monomer capable of polymerizing with the conjugated diene monomer is preferably an aromatic vinyl monomer styrene or α-methylstyrene. In the present invention, the crosslinking monomer is preferably a compound having at least two polymerizable functional groups in the molecule, more preferably allyl methacrylate, divinylbenzene, dimethacrylate compound or diallyl compound. In the present invention, if the amount of crosslinking agent added is too much, the resin will be excessively crosslinked and the impact resistance will be sacrificed. It can be understood that the amount ratio of the crosslinking monomer defined in the present invention is the optimal ratio. In the present invention, the emulsifier is preferably an anionic emulsifier, more preferably sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate, potassium oleate, potassium stearate or potassium disproportionated rosin acid. In the present invention, the oxidant is preferably one or more of potassium persulfate, ammonium persulfate, cumene hydroperoxide (CHP), tert-butyl hydroperoxide (tBHP), hydrogen peroxide, terpene hydroperoxide (PMHP) and dicumyl peroxide (DCP). In the present invention, the electrolyte is preferably one or more of sodium pyrophosphate, calcium phosphate, sodium bicarbonate, potassium chloride, sodium chloride, calcium chloride, aluminum chloride and potassium carbonate. In the present invention, the chain transfer agent is preferably n-dodecyl mercaptan and / or tert-dodecyl mercaptan. In the present invention, the reducing agent is preferably one or more of bisulfite, sulfite, thiosulfate, disulfite and dithionite. In the present invention, the complexing agent is preferably ethylenediaminetetraacetic acid (EDTA), calcium sodium edetate (CaNa2-EDTA) and / or trisodium diethylenetriaminepentaacetate (DTPA).
[0048] In the present invention, the method for preparing the rubber latex preferably comprises the following steps:
[0049] a. Pre-emulsifying the mixture by mixing an emulsifier, an oxidant, an electrolyte, a chain transfer agent, a crosslinking monomer, a vinyl monomer capable of polymerizing with a conjugated diene monomer, and water to obtain a pre-reaction solution;
[0050] b. Under the protection of an inert atmosphere, a conjugated diene monomer is added to the pre-reaction liquid, and after the temperature is raised to the reaction temperature, a reducing agent and a complexing agent are added to react to obtain a rubber latex.
[0051] In the present invention, the reaction temperature in step b is preferably 60-75° C., and the reaction time is preferably 5-20 hours. In the present invention, the average particle size of the prepared rubber latex is preferably 40-60 nm.
[0052] In the present invention, the raw materials for preparing the hard monomer in step 1) preferably include, by weight: 0 to 6 parts of vinyl monomer, 0 to 0.2 parts of cross-linking monomer, 0.05 to 0.3 parts of oxidant, 0 to 6 parts of alkyl methacrylate, 0.01 to 0.5 parts of reducing agent and 0 to 0.3 parts of emulsifier.
[0053] In the present invention, the vinyl monomer is preferably an aromatic vinyl monomer or α-methylstyrene. In the present invention, the alkyl methacrylate is preferably one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate and butyl methacrylate. In the present invention, the raw materials of the vinyl monomer, crosslinking monomer, oxidant, reducing agent and emulsifier are the same as the raw materials for preparing rubber latex. For example, the oxidant is preferably one or more of potassium persulfate, ammonium persulfate, cumene hydroperoxide (CHP), tert-butyl hydroperoxide (tBHP), hydrogen peroxide, terpene hydroperoxide (PMHP) and dicumyl peroxide (DCP).
[0054] The present invention can form a hard shell outside the rubber core by coating the hard monomer outside the rubber latex, which can ensure that the interior has high elasticity and can also ensure that the particle clusters that are gathered but not fused in the subsequent agglomeration process to ensure the impact strength; and can form a closed layer, thereby improving the performance of high-temperature yellowing.
[0055] After obtaining the latex coated with the hard monomer layer, the present invention adds an acidic polymer emulsion to the latex coated with the hard monomer layer for agglomeration to obtain the agglomerated latex. In the present invention, the raw materials for preparing the acidic polymer emulsion in step 2) preferably include, by weight: 85 to 97 parts of alkyl acrylate, 3 to 15 parts of unsaturated acid, 0.5 to 3 parts of emulsifier, 0 to 1 part of electrolyte, 0 to 0.5 parts of chain transfer agent and 0.1 to 1 parts of oxidant. In the present invention, the alkyl acrylate is preferably one or more of methyl acrylate, ethyl acrylate, butyl acrylate and octyl acrylate. In the present invention, the unsaturated acid is preferably one or more of methacrylic acid, acrylic acid, itaconic acid and crotonic acid. In the present invention, the pH of the unsaturated acid emulsion is preferably 4.0 to 4.5. In the present invention, the carboxylic acid group provided by the unsaturated acid can penetrate the emulsified layer of the inner coating layer (hard monomer layer), and the carboxyl group forms a chemical bond with the unsaturated bond of the rubber latex, so that several rubber cores are agglomerated to form a large particle size latex. In the present invention, the average particle size of the agglomerated latex is preferably 120 to 260 nm. In the present invention, the mass ratio of the acidic polymer emulsion to the latex coated with the hard monomer layer is preferably 0.1 to 3:100. In the present invention, if the amount of unsaturated acid is too large, the stability of the agglomeration process will be reduced. It can be understood that the amount ratio of the unsaturated acid defined in the present invention is the optimal ratio. In the present invention, the raw materials for preparing the other raw materials (cross-linking monomer, oxidant, reducing agent and emulsifier) for preparing the hard monomer are selected the same as the raw materials for preparing the rubber latex.
[0056] In the present invention, the acidic polymer emulsion is preferably prepared by the following steps:
[0057] (1) mixing an alkyl acrylate, an unsaturated acid, an emulsifier, an electrolyte, a chain transfer agent, an oxidant and water, and emulsifying the mixture to obtain a pre-emulsion;
[0058] (2) heating 25% to 35% of the total amount of the pre-emulsion obtained in step (1) to 70 to 75° C., heating the system to 80 to 85° C. after the system turns blue, and dripping the remaining pre-emulsion into the heated pre-emulsion to obtain an acidic polymer emulsion.
[0059] After obtaining the agglomerated latex, the present invention performs grafting on the agglomerated latex to obtain MBS resin. In the present invention, the raw materials for grafting in step 3) preferably include, by weight: 4 to 18 parts of alkyl methacrylate, 6 to 22 parts of aromatic vinyl monomer, 0.1 to 1 part of emulsifier, 0.05 to 0.7 part of oxidant, 0 to 0.25 part of electrolyte, 0.01 to 0.5 part of reducing agent, 0 to 0.25 part of chain transfer agent and 0 to 1 part of crosslinking monomer. In the present invention, the raw material selection of the raw material for grafting is the same as the raw material selection for preparing rubber latex, hard monomer, etc.
[0060] In the present invention, it is preferred to carry out grafting on the agglomerated latex by continuous feeding or intermittent feeding.
[0061] In the present invention, the continuous feeding method is preferably: mixing the grafted raw materials, adding the obtained mixed material to the agglomerated latex for grafting reaction, and obtaining the MBS resin;
[0062] In the present invention, the intermittent feeding method preferably comprises the following steps:
[0063] ① Add part of the oxidant and chain transfer agent to the agglomerated latex, and continuously drop a mixed emulsion of aromatic vinyl monomer, water, part of the emulsifier, part of the reducing agent and electrolyte to carry out a grafting reaction.
[0064] Obtaining a pre-product of MBS resin;
[0065] ② Add the remaining oxidant to the pre-product of MBS resin, and then continuously drop a mixed emulsion of alkyl methacrylate, water, the remaining emulsifier, the remaining reducing agent and the cross-linking agent to carry out a grafting reaction to obtain MBS resin.
[0066] In the present invention, the temperature for the grafting reaction is preferably 75 to 90° C., and the time is preferably 2 to 10 hours. In the present invention, the particle size of the prepared MBS resin is preferably 180 to 280 nm.
[0067] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0068] Example 1
[0069] 1. Preparation of Rubber Latex
[0070] 1.49 parts of potassium oleate, 0.84 parts of cumene hydroperoxide, 0.49 parts of sodium bicarbonate, 0.94 parts of n-dodecyl mercaptan and 100 parts of water were added to the reactor and stirred for 10 minutes to obtain a pre-reaction solution. The reactor was then purged three times with nitrogen to remove the oxygen in the reactor, and 100 parts of butadiene were pumped into the reactor. After the temperature of the reactor was stabilized to 60°C, 0.28 parts of sodium formaldehyde sulfoxylate, 0.0015 parts of ferrous sulfate solution, and 0.003 parts of ethylenediaminetetraacetic acid were added, and the pressure of the reactor was controlled at 0.68Mpa. The reaction was continued for 20 hours to obtain a rubber latex with an average particle size of 54nm, and the polymerization conversion rate was 96%.
[0071] 2. Coating hard monomer
[0072] To 68 parts (solid amount) of the above rubber latex, add 76.6 parts of deionized water. When the temperature rises to 75°C, add 0.0715 parts of tBHP, and add dropwise a mixed solution of 5 parts of styrene, 5 parts of methyl methacrylate, 10 parts of deionized water, 0.142 parts of sodium dodecylbenzene sulfonate and 0.05 parts of sodium formaldehyde sulfoxylate. The mixture is reacted for 3 hours to obtain a latex coated with a hard monomer layer with an average particle size of 56 nm.
[0073] 3. Synthetic acid polymer emulsion
[0074] 85 parts of butyl acrylate, 15 parts of methacrylic acid, 1 part of sodium dodecyl sulfonate, 0.25 parts of potassium carbonate, 0.2 parts of n-dodecyl mercaptan, 0.5 parts of potassium persulfate and 167 parts of deionized water were added to a four-necked bottle and emulsified for 30 minutes to obtain a pre-emulsion. 30wt% of the pre-emulsion was heated to 75°C, and after the system turned blue, the temperature was raised to 82°C, and the remaining pre-emulsion was continuously added dropwise for 5.5 hours, and the temperature was kept for 1 hour to obtain an acidic polymer emulsion.
[0075] 4. Agglomeration
[0076] 78 parts (solid weight) of latex coated with a hard monomer layer were heated to 80°C, 1.17 parts (solid weight) of the acidic polymer emulsion prepared above were added, and the mixture was stirred and heated at 75°C for 30 minutes to obtain an agglomerated latex with an average particle size of 198 nm.
[0077] 5. Graft polymerization
[0078] 0.0976 parts of tBHP, 0.0688 parts of n-dodecyl mercaptan were added to the above 78 parts of agglomerated latex, and a mixed emulsion of 13.7 parts of styrene, 13.7 parts of deionized water, 0.233 parts of sodium dodecylbenzene sulfonate, 0.0688 parts of sodium formaldehyde sulfoxylate, and 0.106 parts of sodium bicarbonate was continuously added dropwise, and the mixture was reacted at 78°C for 5 hours. 0.059 parts of tBHP were then added thereto, and a mixed emulsion of 8.3 parts of methyl methacrylate, 8.3 parts of deionized water, 0.165 parts of sodium dodecylbenzene sulfonate, 0.04 parts of sodium formaldehyde sulfoxylate, and 0.08 parts of divinylbenzene was continuously added dropwise, and the mixture was reacted at 78°C for 4 hours to obtain MBS latex with a conversion rate of 99% and an average particle size of 210 nm.
[0079] Example 2
[0080] The difference from Example 1 is that the operation during graft polymerization is different, wherein the specific steps during graft polymerization are as follows:
[0081] To the above 78 parts of agglomerated latex, add 0.0976 parts of tBHP and 0.0688 parts of n-dodecyl mercaptan, and continuously drop a mixed emulsion of 11 parts of styrene, 11 parts of methyl methacrylate, 22 parts of deionized water, 0.4 parts of sodium dodecylbenzene sulfonate, 0.11 parts of sodium formaldehyde sulfoxylate and 0.106 parts of sodium bicarbonate. The mixture is reacted at 78°C for 5 hours to obtain MBS latex with a conversion rate of 99% and an average particle size of 226 nm.
[0082] Example 3
[0083] The difference from Example 1 is that the operation during graft polymerization is different, wherein the specific steps during graft polymerization are as follows:
[0084] To the above 78 parts of the agglomerated latex, 0.0976 parts of tBHP, 0.0688 parts of n-dodecyl mercaptan, and styrene pre-emulsion (styrene pre-emulsion consists of 11 parts of styrene, 11 parts of deionized water, 0.2 parts of sodium dodecylbenzene sulfonate, 0.055 parts of sodium bicarbonate and 0.055 parts of sodium formaldehyde sulfoxylate) are continuously added dropwise. When the styrene pre-emulsion is added to 4 / 5, a mixed emulsion of 11 parts of methyl methacrylate, 11 parts of deionized water, 0.4 parts of sodium dodecylbenzene sulfonate, 0.055 parts of sodium bicarbonate, and 0.055 parts of sodium formaldehyde sulfoxylate is added to the remaining 1 / 5 of the styrene pre-emulsion, and stirred to obtain a mixture, and the mixture is added dropwise to the agglomerated latex (wherein, during the mixing and stirring to prepare the mixture, the styrene pre-emulsion is continuously added dropwise to the agglomerated latex); the reaction is carried out at 78°C for 5 hours to obtain MBS latex with a conversion rate of 99% and an average particle size of 224 nm.
[0085] Example 4
[0086] 1. Preparation of Rubber Latex
[0087] 4 parts of sodium dodecyl sulfate, 1.2 parts of cumene hydroperoxide, 1.2 parts of sodium pyrophosphate, 1.5 parts of tert-dodecyl mercaptan, 150 parts of water and 50 parts of styrene were added to the reactor and stirred for 10 minutes to obtain a pre-reaction solution. The reactor was then purged with nitrogen three times to remove the oxygen in the reactor, and 50 parts of butadiene were pumped into the reactor. After the temperature of the reactor was stabilized to 75°C, 0.5 parts of sodium formaldehyde sulfoxylate, 0.006 parts of ferrous sulfate solution, and 0.012 parts of EDTA were added, and the pressure of the reactor was controlled at 0.5 MPa. The reaction was continued for 10 hours to obtain a rubber latex with an average particle size of 40 nm and a polymerization conversion rate of 89%.
[0088] 2. Coating hard monomer
[0089] To 60 parts (solid amount) of the above rubber latex, add 76.6 parts of deionized water. When the temperature rises to 85°C, add 0.0715 parts of CHP. Add dropwise a mixed solution of 4 parts of methyl methacrylate, 10 parts of deionized water, 0.142 parts of sodium dodecylbenzenesulfonate and 0.05 parts of sodium formaldehyde sulfoxylate. React for 1.5 hours to obtain a latex coated with a hard monomer layer with an average particle size of 41 nm.
[0090] 3. Synthetic acid polymer emulsion
[0091] 97 parts of butyl methacrylate, 3 parts of acrylic acid, 3 parts of sodium dodecyl sulfonate, 1 part of potassium carbonate, 0.5 parts of n-dodecyl mercaptan, 0.5 parts of potassium persulfate and 167 parts of deionized water were added to a four-necked bottle and emulsified for 30 minutes to obtain a pre-emulsion. 30wt% of the pre-emulsion was heated to 70°C, and after the system turned blue, the temperature was raised to 80°C, and the remaining pre-emulsion was continuously added dropwise for 5.5 hours, and the temperature was kept for 1 hour to obtain an acidic polymer emulsion.
[0092] 4. Agglomeration
[0093] 64 parts (solid weight) of latex coated with a hard monomer layer were heated to 80°C, and 2.34 parts (solid content) of the acidic polymer emulsion prepared above were added, and stirred and heated at 75°C for 30 minutes to obtain an agglomerated latex with an average particle size of 178 nm.
[0094] 5. Graft polymerization
[0095] 0.36 parts of tBHP and 0.1 parts of n-dodecyl mercaptan were added to the above 64 parts of agglomerated latex, and a mixed emulsion of 20 parts of styrene, 20 parts of deionized water, 0.56 parts of sodium dodecylbenzene sulfonate, 0.2 parts of sodium formaldehyde sulfoxylate, and 0.106 parts of sodium bicarbonate was continuously added dropwise, and the mixture was reacted at 85°C for 3 hours. 0.25 parts of tBHP were then added thereto, and a mixed emulsion of 16 parts of methyl methacrylate, 16 parts of deionized water, 0.44 parts of sodium dodecylbenzene sulfonate, 0.12 parts of sodium formaldehyde sulfoxylate, and 0.08 parts of divinylbenzene was continuously added dropwise, and the mixture was reacted at 75°C for 2 hours to obtain MBS latex with a conversion rate of 99% and an average particle size of 202 nm.
[0096] Example 5
[0097] 1. Preparation of Rubber Latex
[0098] 0.75 parts of potassium rosinate, 0.5 parts of potassium persulfate, 0.25 parts of sodium pyrophosphate, 1.2 parts of n-dodecyl mercaptan and 100 parts of water were added to the reactor and stirred for 10 minutes to obtain a pre-reaction solution. The reactor was then purged three times with nitrogen to remove the oxygen in the reactor, and 100 parts of butadiene were pumped into the reactor. After the temperature of the reactor was stabilized to 60°C, 0.1 parts of sodium formaldehyde sulfoxylate, 0.0011 parts of ferrous sulfate solution, and 0.0022 parts of ethylenediaminetetraacetic acid were added, and the pressure of the reactor was controlled at 0.65Mpa. The reaction was continued for 12 hours to obtain a rubber latex with an average particle size of 43nm, and a polymerization conversion rate of 96%.
[0099] 2. Coating hard monomer
[0100] To 80 parts (solid amount) of the above rubber latex, add 76.6 parts of deionized water. When the temperature rises to 75°C, add 0.0715 parts of DCP, and drop 5 parts of styrene, 0.1 parts of divinylbenzene, 5 parts of deionized water, 0.142 parts of sodium dodecylbenzene sulfonate, and 0.05 parts of a mixed solution of sodium formaldehyde sulfoxylate. React for 3 hours to obtain a latex coated with a hard monomer layer.
[0101] 3. Synthetic acid polymer emulsion
[0102] 60 parts of butyl acrylate, 30 parts of butyl methacrylate, 10 parts of methacrylic acid, 1.8 parts of sodium dodecyl sulfonate, 0.75 parts of potassium carbonate, 0.5 parts of n-dodecyl mercaptan, 1 part of potassium persulfate and 167 parts of deionized water were added to a four-necked bottle and emulsified for 30 minutes to obtain a pre-emulsion. 35wt% of the pre-emulsion was heated to 75°C, and after the system turned blue, the temperature was raised to 85°C, and the remaining pre-emulsion was continuously added dropwise for 5.5 hours, and the temperature was kept for 1 hour to obtain an acidic polymer emulsion.
[0103] 4. Agglomeration
[0104] 85 parts (solid weight) of latex coated with a hard monomer layer were heated to 80°C, and 2.34 parts of the acidic polymer emulsion prepared above were added, and stirred and heated at 75°C for 30 minutes to obtain an agglomerated latex with an average particle size of 258 nm.
[0105] 5. Graft polymerization
[0106] To the above 85 parts of agglomerated latex, add 0.06tBHP, 0.075 parts of n-dodecyl mercaptan, and continuously drop a mixed emulsion of 9 parts of styrene, 6 parts of methyl methacrylate, 22 parts of deionized water, 0.5 parts of sodium dodecylbenzene sulfonate, 0.043 parts of sodium formaldehyde sulfoxylate and 0.08 parts of sodium bicarbonate. React at 85°C for 2h and keep warm at 90°C for 1h to obtain MBS latex with a conversion rate of 99% and an average particle size of 263nm.
[0107] Comparative Example 1
[0108] 1. Preparation of Rubber Latex
[0109] 1.49 parts of potassium oleate, 0.84 parts of cumene hydroperoxide, 0.49 parts of sodium bicarbonate, 0.94 parts of n-dodecyl mercaptan and 100 parts of water were added to the reactor and stirred for 10 minutes to obtain a pre-reaction solution. The reactor was then purged three times with nitrogen to remove the oxygen in the reactor, and 100 parts of butadiene were pumped into the reactor. After the temperature of the reactor was stabilized to 60°C, 0.28 parts of sodium formaldehyde sulfoxylate, 0.0015 parts of ferrous sulfate solution, and 0.003 parts of ethylenediaminetetraacetic acid were added, and the pressure of the reactor was controlled at 0.68Mpa. The reaction was continued for 20 hours to obtain a rubber latex with an average particle size of 54nm, and the polymerization conversion rate was 96%.
[0110] 2. Synthetic acid polymer emulsion
[0111] 85 parts of butyl acrylate, 15 parts of methacrylic acid, 1 part of sodium dodecyl sulfonate, 0.25 parts of potassium carbonate, 0.2 parts of n-dodecyl mercaptan, 0.5 parts of potassium persulfate and 167 parts of deionized water were added to a four-necked bottle and emulsified for 30 minutes to obtain a pre-emulsion. 30wt% of the pre-emulsion was heated to 75°C, and after the system turned blue, the temperature was raised to 82°C, and the remaining pre-emulsion was continuously added dropwise for 5.5 hours, and the temperature was kept for 1 hour to obtain an acidic polymer emulsion.
[0112] 3. Agglomeration
[0113] 68 parts (solid weight) of latex were heated to 80°C, 1.17 parts (solid weight) of the acidic polymer emulsion prepared above were added, and the mixture was stirred and heated at 75°C for 30 minutes to obtain an agglomerated latex with an average particle size of 212 nm.
[0114] 4. Graft polymerization
[0115] 0.11 parts of tBHP and 0.079 parts of n-dodecyl mercaptan were added to the above 68 parts of agglomerated latex, and a mixed emulsion of 18.7 parts of styrene, 18.7 parts of deionized water, 0.318 parts of sodium dodecylbenzene sulfonate, 0.094 parts of sodium formaldehyde sulfoxylate, and 0.1447 parts of sodium bicarbonate was continuously added dropwise, and the mixture was reacted at 78°C for 5 hours. 0.08 parts of tBHP was then added thereto, and a mixed emulsion of 13.3 parts of methyl methacrylate, 13.3 parts of deionized water, 0.259 parts of sodium dodecylbenzene sulfonate, 0.064 parts of sodium formaldehyde sulfoxylate, and 0.128 parts of divinylbenzene was continuously added dropwise, and the mixture was reacted at 78°C for 4 hours to obtain MBS latex with a conversion rate of 99% and an average particle size of 232 nm.
[0116] Comparative Example 2
[0117] The difference from Example 2 is that 6 parts of divinylbenzene are added in the rubber synthesis stage, and 1.5 parts of divinylbenzene are added in the graft polymerization stage. The other operation steps are the same as those in Example 2.
[0118] Among them, the specific steps of the rubber synthesis stage are as follows:
[0119] 1.49 parts of potassium oleate, 0.84 parts of cumene hydroperoxide, 0.49 parts of sodium bicarbonate, 0.94 parts of n-dodecyl mercaptan, 6 parts of divinylbenzene and 100 parts of water were added to the reactor and stirred for 10 minutes to obtain a pre-reaction solution. The reactor was then purged three times with nitrogen to remove the oxygen in the reactor, and 100 parts of butadiene were pumped into the reactor. After the reactor temperature stabilized to 60°C, 0.28 parts of sodium formaldehyde sulfoxylate, 0.0015 parts of ferrous sulfate solution, and 0.003 parts of ethylenediaminetetraacetic acid were added, and the reactor pressure was controlled at 0.68Mpa. The reaction was continued for 20 hours to obtain a rubber latex with an average particle size of 44nm, and the polymerization conversion rate was 96%.
[0120] The specific steps of graft polymerization are as follows:
[0121] To the above 78 parts of agglomerated latex, add 0.0976 parts of tBHP, 0.0688 parts of n-dodecyl mercaptan, and continuously drop a mixed emulsion of 11 parts of styrene, 11 parts of methyl methacrylate, 22 parts of deionized water, 0.4 parts of sodium dodecylbenzene sulfonate, 0.11 parts of sodium formaldehyde sulfoxylate, 0.106 parts of sodium bicarbonate, and 1.5 parts of divinylbenzene. The mixture is reacted at 78°C for 5 hours to obtain MBS latex with a conversion rate of 99% and an average particle size of 264 nm.
[0122] Comparative Example 3
[0123] The difference from Example 1 is that the operation mode during agglomeration is different, and other operations are the same as Example 1. Among them, the specific operations during agglomeration are as follows:
[0124] Add 78 parts of latex coated with a hard monomer layer to a three-necked flask with stirring, and start stirring. Slowly add a 0.7% sulfuric acid solution until the pH of the emulsion drops to 5.5, and continue to add a 1% sodium hydroxide solution to the emulsion until the pH increases to 10. Repeat the above operation of adding acid and alkali until the final average particle size reaches 140nm. (The principle is that adding acid makes the emulsifier ineffective, the system unstable, and the particle size increases. Then add alkali to adjust the pH of the system and stabilize the system again. Then repeat the addition of acid and alkali until the particle size of the system increases to the desired particle size.)
[0125] The agglomerated latex was grafted, and the grafting operation was the same as in Example 1, and finally an MBS emulsion with a particle size of 147 nm was obtained.
[0126] Comparative Example 4
[0127] The difference from Example 1 is that the operation mode during agglomeration is different, and other operations are the same as Example 1. Among them, the specific operations during agglomeration are as follows:
[0128] 78 parts of latex coated with a hard monomer layer were added to a three-necked flask with stirring, and stirring was started. 15.6 g of 0.4% diluted sulfuric acid was slowly added dropwise, followed by 12.5 g of 0.7% diluted sulfuric acid, until the average particle size reached 96 nm.
[0129] The agglomerated latex was grafted, and the grafting operation was the same as in Example 1, and finally an MBS emulsion with a particle size of 103 nm was obtained.
[0130] Performance Testing
[0131] The performance of the MBS latex prepared in each embodiment and comparative example was tested, and the specific test results are shown in Table 1.
[0132] in:
[0133] Particle size test: Take a small amount of MBS latex and dilute it 3 times with deionized water, and drop the mixed diluted latex into the sample pool until the light shielding reaches 8%. Put the sample pool into the laser particle size analyzer for testing at a speed of 1800r / min. Test each sample 3 times and take the average value.
[0134] Yellowness test standard: 100 PC (Trinseo EMERGE TM 8600PV) and 10 parts of MBS were mixed evenly, extruded, and injection molded into a 4 mm thick color plate at 260 ° C. and heat retained for 8 minutes, and then tested according to ASTM E313-10 standard.
[0135] Impact strength test: 100 parts of PC (Trinseo EMERGE TM 10 parts of MBS powder, 0.1 parts of antioxidant 1076 and 0.1 parts of antioxidant 168 were added to 8600PV, and after extrusion and injection molding, the impact strength was tested according to ISO 180 standard.
[0136] Table 1
[0137]
[0138] It can be seen from Table 1 that compared with other embodiments, Example 4 uses less butadiene to play a toughening role when preparing rubber latex, resulting in lower impact strength than other embodiments. Compared with Examples 1 to 3, Example 1 does not coat the rubber latex with a hard monomer layer, and the impact strength of the MBS resin obtained is significantly reduced, and the yellowness index is significantly increased. In Example 2, more cross-linking monomers are added, resulting in excessive cross-linking of the resin, thereby sacrificing some impact resistance, and the resin strength is significantly reduced. In Examples 3 and 4, the agglomeration method is changed, and the particle size is increased by adding acid. The product obtained in this way has a high yellowness index and poor product quality.
[0139] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A MBS resin, characterized in that: It comprises a rubber core and a shell layer, wherein the shell layer comprises a hard monomer layer and a thermoplastic resin layer; The hard monomer layer is wrapped on the rubber core to obtain a latex coated with the hard monomer layer, the acid polymer emulsion agglomerates a plurality of latexes coated with the hard monomer layer to form an agglomerated latex, and the thermoplastic resin layer is wrapped on the agglomerated latex; The total weight of the rubber core, the hard monomer layer and the thermoplastic resin layer is 100 parts, including 60 to 80 parts of the rubber core, 1 to 10 parts of the hard monomer layer and 10 to 40 parts of the thermoplastic resin layer; The raw materials of the hard monomer layer include vinyl monomers and / or alkyl methacrylate; the thermoplastic resin layer is obtained by grafting alkyl methacrylate and aromatic vinyl monomer; the raw materials of the acidic polymer emulsion include alkyl acrylate and unsaturated acid.
2. The MBS resin according to claim 1, characterized in that The rubber core is obtained by polymerizing a conjugated diene monomer, or by polymerizing a conjugated diene monomer and a vinyl monomer that can polymerize with the conjugated diene monomer.
3. The MBS resin according to claim 2, characterized in that The raw materials for preparing the rubber core include, by weight: 50-100 parts of conjugated diene monomer, 0-50 parts of vinyl monomer capable of polymerizing with conjugated diene monomer, 0-1.5 parts of chain transfer agent and 0-5 parts of crosslinking monomer, 0.5-4 parts of emulsifier, 0.5-1.2 parts of oxidant, 0-1.2 parts of electrolyte, 0.001-0.5 of reducing agent and 0.002-0.15 parts of complexing agent.
4. The MBS resin according to claim 1, characterized in that By weight, the raw materials for preparing the hard monomer include: 0 to 6 parts of vinyl monomer, 0 to 0.2 parts of crosslinking monomer, 0.05 to 0.3 parts of oxidant, 0 to 6 parts of alkyl methacrylate, 0.01 to 0.5 parts of reducing agent and 0 to 0.3 parts of emulsifier.
5. The MBS resin according to claim 1, characterized in that The raw materials for preparing the acidic polymer emulsion include, by weight: 85-97 parts of alkyl acrylate, 3-15 parts of unsaturated acid, 0.5-3 parts of emulsifier, 0-1 part of electrolyte, 0-0.5 part of chain transfer agent and 0.1-1 part of oxidant.
6. The MBS resin according to claim 1, characterized in that By weight, the raw materials for grafting include: 4-18 parts of alkyl methacrylate, 6-22 parts of aromatic vinyl monomer, 0.1-1 parts of emulsifier, 0.05-0.7 parts of oxidant, 0-0.25 parts of electrolyte, 0.01-0.5 parts of reducing agent, 0-0.25 parts of chain transfer agent and 0-1 parts of crosslinking monomer.
7. The MBS resin according to claim 1, characterized in that The mass ratio of the acid polymer emulsion to the latex coated with the hard monomer layer is 0.1 to 3:
100.
8. The MBS resin according to claim 1, characterized in that The particle size of the rubber core is between 40 and 60 nm; the particle size of the latex after agglomeration is between 120 and 260 nm; and the particle size of the MBS resin is between 180 and 280 nm.
9. The method for preparing the MBS resin according to any one of claims 1 to 8, characterized in that: The steps include: 1) using rubber latex as a rubber core and coating the rubber latex with a hard monomer to obtain a latex coated with a hard monomer layer; 2) adding an acidic polymer latex to the latex coated with the hard monomer layer for agglomeration to obtain an agglomerated latex; 3) Grafting is performed on the agglomerated latex to obtain MBS resin.
10. The preparation method according to claim 9, characterized in that: The preparation method of the rubber latex described in step 1) comprises the following steps: a. Pre-emulsifying the mixture by mixing an emulsifier, an oxidant, an electrolyte, a chain transfer agent, a crosslinking monomer, a vinyl monomer capable of polymerizing with a conjugated diene monomer, and water to obtain a pre-reaction solution; b. Under the protection of an inert atmosphere, a conjugated diene monomer is added to the pre-reaction liquid, and after the temperature is raised to the reaction temperature, a reducing agent and a complexing agent are added to react to obtain a rubber latex.
11. The preparation method according to claim 9, characterized in that: The acidic polymer emulsion in step 2) is prepared by the following steps: (1) mixing an alkyl acrylate, an unsaturated acid, an emulsifier, an electrolyte, a chain transfer agent, an oxidant and water, and emulsifying the mixture to obtain a pre-emulsion; (2) heating 25% to 35% of the total amount of the pre-emulsion obtained in step (1) to 70 to 75° C., heating the system to 80 to 85° C. after the system turns blue, and dripping the remaining pre-emulsion into the heated pre-emulsion to obtain an acidic polymer emulsion.
12. The preparation method according to claim 9, characterized in that: In step 3), grafting is performed on the agglomerated latex by continuous or intermittent feeding; The continuous feeding method is: mixing the grafted raw materials, adding the obtained mixed material into the agglomerated latex to carry out grafting reaction, and obtaining the MBS resin; The intermittent feeding method comprises the following steps: ① Adding part of the oxidant and the chain transfer agent to the agglomerated latex, and continuously dropping a mixed emulsion of aromatic vinyl monomer, water, part of the emulsifier, part of the reducing agent and electrolyte to carry out a grafting reaction to obtain a pre-product of MBS resin; ② Add the remaining oxidant to the pre-product of MBS resin, and then continuously drop a mixed emulsion of alkyl methacrylate, water, the remaining emulsifier, the remaining reducing agent and the cross-linking agent to carry out a grafting reaction to obtain MBS resin.
Citation Information
Cited By
Preparation method of impact-resistant wear-resistant PMMA (polymethyl methacrylate) casting plate and PMMA casting plate
CN120923954A